APLIKASI ARSITEKTUR METAFORA PADA STRATEGI PERANCANGAN LEMBAGA PENDIDIKAN MUSIK DI SURABAYA - Ajeng Cita Anggraini; Rachmadi Nugroho; Suparno Suparno (ARSITEKTURA, 2017)
The design proposal of Music School in Surabaya arises from society’s increasing interest in the art of music, significant growth of Indonesian music industry which promises anyone involved likely gain, and underdeveloped infrastructure of the numerous, existing music school in Surabaya to cater the need in a bigger scale. Hence, the proposal focuses on the issue of designing Music School in Surabaya which provides space for music- and informal-music-education-related activities. It aims to serve as the place to learn music theories and perform musical art. The metaphorical architecture approach is applied to the design in order to reflect the function of the building. In other words, building observer will have ideas about the activities occurred inside through the façade which utilised the stated design approach. Keywords: Metaphorical Architecture, Education Institute, Music, Surabaya